Information Consumption Patterns of Generation Z in the Era of Digital Media Convergence - Arinil Hidayah; Muhammad Anshar (LP3M KH Yazid Karimullah Institute, 2025)
This research was conducted because the development of digital media that affects the way of processing information has shifted among gen Z, therefore, this research is to find out how gen Z's information consumption patterns in the era of digital media convergence. The research method used is a descriptive qualitative approach with literature study analysis techniques, by analyzing documents such as books, journals and research results. Thus, this research shows that generation Z has its own way of communicating and receiving information as the highest internet user, especially social media 89%, they use social media as a tool to gather the latest news information without looking for it in online newspapers, as well as personal information needs such as education, social networking and career. Unfortunately, quite a few of them put forward a critical mindset in consuming information by comparing other information variables, so that most of them only judge from the level of information speed and validation of viewers from their online networks, causing gen Z's critical power to tend to be low. Gen Z indirectly creates its social identity through preference patterns in using digital media.